Quantification of Sensitization in Aluminum–Magnesium Alloys Through Frequency-Dependent Ultrasonic Attenuation - Songwei Wang; Haiying Huang (Sensors)
Aluminum–Magnesium (Al–Mg) alloys undergo sensitization, i.e., the precipitations of β-phase (Al2Mg3) at the grain boundaries, when exposed to elevated temperature. This microstructural change increases the susceptibility of Al–Mg alloys to intergranular corrosion, exfoliation, and stress corrosion cracking. This study introduces a time-frequency analysis (TFA) technique to determine the frequency-dependent ultrasonic attenuation parameter and correlate the frequency-attenuation slope to the Degree of Sensitization (DoS) developed in heat-treated Al–Mg alloy samples. Broadband pitch-catch signal was generated using a laser ultrasonic testing (LUT) system, from which the narrowband pitch-catch signal at different frequencies can be digitally generated. The attenuation parameters of sensitized Al–Mg samples were determined from these narrowband pitch-catch signals using the primary pulse-first echo (PP-FE) method. By identifying the frequency range within which the attenuation parameter is linearly proportional to the frequency, the slopes of the frequency-attenuation relationship were determined and correlated with the DoS values of the sample plates. The experimental results validate that the frequency-attenuation slope has a higher sensitivity and lower scattering as compared to other conventional ultrasonic attenuation measurement techniques.